Physical features and management of migratory Nari cattle population of Rajasthan - Singh, PK; Pundir, RK; Sadana, D.K.; Rathore, H.S. (Journal of Livestock Biodiversity, 2025)
The Nari cattle are maintained as migratory herds in Pali and Sirohi districts of Rajasthan. In this study phenotypic characterization of the Nari cattle was carried out through systematic survey in its breeding tract and the breed descriptors were developed for its registration as a distinct breed. The population of Nari cattle in the breeding tract is expected to be more than 50,000. Nari cattle have compact body and are strong and active. The cows are generally white or grey in coat colour; the bulls are white, dark grey or black in colour. Biometry of 354 animals, which included nine diﬀerent body measurements in diﬀerent age and sex groups, was recorded. When compared with Kankrej breed of cattle, the body measurements viz. body length, height at withers, chest girth and paunch girth of Nari cattle are lower. The average horn length of Nari cattle was 51.68 cm, which is more than Kankrej and other indigenous cattle breeds. The circumference of horn at base is larger in Kankrej cattle than in Nari. This indicated that Nari cattle may be having the longest horn compared with all the indigenous cattle breeds of India. The animals are kept in big herds with size varying from 20-100 animals under pastoral production system as well as under extensive production system as stationary herds. The average age at irst calving was 3.5 to 4.5 years with a calving interval of 1.25 to 2 years. On an average the bulls start mating at the age of 3.0 to 3.5 years and used for breeding up to around 10 years of the age. The life span of the animals was around 20 years with life time number of calvings of 8-10. It was observed that the peak milk yield of Nari cows ranged from 3 to 8 kg. Animals of this breed are playing a signi icant role in the rural livelihood of Raika community in terms of milk and bullocks power for agricultural operations. This cattle population has not been included in the list of recognized cattle breeds of India. The unique physical features, biometry and their production system makes Nari cattle population as having distinct identity, therefore, may be registered as a new cattle breed of India. Keeping in view the declining population status of Nari cattle, there is a need to take up sustainable measures for its genetic improvement and conservation.